Rekwizyt w świecie pojęć - Krajewska, Anna (Przestrzenie Teorii, 2023)
This introductory article deals with the different ways of representing the prop: from an object referring to meaning, which is mainly related to the theatrical stage, to the notion of a prop playing the role of an analytical category in literary studies.